Travellers' tales narratives of home and displacement (Futures : New perspectives for cultural analysis, 1994)
"Travellers' Tales is the second of a series which brings together theorists from different disciplines to assess the implications of economic, political and social change for intellectual enquiry and cultural practice. The series arises from and continues the concerns of BLOCK (1979 to 1989), the journal of visual culture." "Most of us, at various moments in our lives, either adopt a tourist identity or are 'framed' within another's tourist experience. Travellers' Tales investigates the future for travelling in a world whose boundaries are shifting and dissolving. The contributors bring together popular and critical discourses of travel to explore questions of identity and politics; history and narration, collecting and representing other cultures." "Travellers' tales oscillate between the thrill of novel experiences and unexpected pleasures, and the alienation and loneliness of exile in a strange land. The contributions review recent work on the discourses of tourism, travel and cultural politics; the effects of global interactions and local resistances; and the ways in which records, memorials and signs have all been used to describe the experience of encountering the 'other'."--BOOK JACKET.